Quantum molecular modeling of hepatitis C virus inhibition through non-structural protein 5B polymerase receptor binding of C5-arylidene rhodanines. (April 2018) - Balasubramanian, Krishnan; Patil, Vaishali M.
Graphical abstract: High-level quantum chemical computations were accompanied by molecular docking studies to provide insights into the binding modes for a set of 18 C5 -arylidene rhodanine isomers as HCV NS5B polymerase inhibitors. The selected rhodanine analogs have been optimized to investigate the multi-target profile by quantum chemical optimization of the geometries and docking of each rhodanine isomer at multiple binding pockets (PP-I, PP-II, TP-I and TP-II). The binding affinity has been analyzed for all the 18 isomers of 2-[(5Z)-5-(2, 4-dichlorobenzylidene)-4-oxo-2-thioxo-1, 3-thiazolidin-3-yl]-3-phenylpropanoic acid and these isomers were ranked on the basis of their binding propensity at the different pockets. The identified four isomers with comparable binding and inhibition compared to the standard (1, 3)- di chloro substituted isomer (IC50 = 10.6 μM) as "multi-targeted drug" candidates. Highlights: Quantum chemical computations and molecular docking studies. Optimization of the multi-target profile of selected rhodanine analogs. Identification of four promising NNI isomers. Provides platform for rational design of potent HCV NS5B polymerase inhibitors. Abstract: We have carried out high-level quantum chemical computations followed by molecular docking studies on a set of 17C5 -arylidene rhodanine isomers to provide insights into the binding modes with different reported binding pockets of the nonstructural protein 5B (NS5B) polymerase that contribute to the hepatitis C virus (HCV) inhibition. We optimized the multi-target profile of the selected rhodanine analogs to investigate potential non-nucleotide inhibitors (NNIs) by quantum chemical optimization of the 18 isomers followed by docking with quantum chemically optimized structures of each isomer with NS5B polymerase at multiple binding pockets. The binding affinities of the PP-I, PP-II and TP-II pockets of NS5B polymerase were analyzed for all the 17 isomers of 2-[(5 Z )-5-(2, 4- di chlorobenzylidene)-4-oxo-2-thioxo-1, 3-thiazolidin-3-yl]-3-phenylpropanoic acid. On the basis of binding propensity at the different pockets and inhibitor constants, we ranked these isomers as potential candidates for the HCV inhibition. We have identified four isomers as promising NNIs of NS5B polymerase with comparable binding and inhibition to the standard (1, 3) di chloro substituted isomer that exhibits in vitro activity and several other isomers as candidates in a "multi-targeted drug" approach.